Effect of skill decomposition on racket and ball kinematics of the elite junior tennis serve - Reid, M.; Whiteside, D.; Elliott, B. (Sports Biomechanics, 2010)
Whole body kinematics of the tennis serve have been reported extensively in the literature, yet comparatively less information exists regarding the kinematic characteristics of the swing and toss. In attempting to develop consistency in placement of the toss and racket trajectory, coaches will often decompose the serve and practice it in separate parts. A 22-camera VICON MX motion analysis system, operating at 250 Hz, captured racket, ball and hand kinematics of the serves of five elite junior players under three conditions. The conditions were flat first serves (FS) directed to a 1 times 1 m target bordering the 'T' of the deuce service box, a ball toss (BT) in isolation and a free swing (SW) in isolation. Players were instructed to perform BT and SW as in the FS. Paired t-tests assessed within-group differences in hand, racket and ball kinematics between the discrete skill and the two decomposed conditions. Vertical displacement of the ball at its zenith increased significantly during BT compared with the FS and temporal associations between racket and ball motion during the FS (r = 0.861) were affected during task decomposition. This study questions the pervasive use of task decomposition in the development of the tennis serve.